CdSe quantum dots using polyselenide precursor in soft chemical conditions - Garcia, Arlindo M. Fontes (2012)
CdSe quantum dots were prepared by a simple microemulsion templating technique at low temperature and using common inorganic precursors. Size control was obtained by small variations in reactant concentrations. The chalcogenide source was a polyselenide solution. Narrow (30-40nm fwhm) band gap photoluminescence low defect level and high quantum yield were obtained.